The use of sociodrama in learning about the concept of social organization in high school social studies - Madlangbayan, Kriemhilda Mejica 1936- (1977)
This seminar paper hopes to give both students and teachers of social studies an idea of how they can bring life to a classroom. The researcher worked on the hypothesis tha a sociodrama can stimulate student activity, critical thinking, and active participation. This is limited for the development of the concept of the social organization for first year high school social studies.
Vita.
Thesis (M.A. Social Studies Education)--University of the Philippines, Diliman.
Keywords: Social sciences -- Study and teaching (Secondary) -- Philippines; Sociodrama; Teaching -- Philippines -- Aids and devices